IMPLEMENTATION OF ORGANIZATIONAL ARRANGEMENT POLICIES REGIONAL SECRETARIAT OF DEPOK CITY WEST JAVA PROVINCE - Ristika Yulianti Gredenggo; Ismail Nurdin; Rizki Amalia (Sean Institute, 2023)
Administration of government in improving welfare described in the policy is expected to create good coordination in the Implementation of Structuring Policies in Regional Secretariat Organizations. This study aims to analyze how the implementation of policies on organizational management of the Regional Secretariat of Depok City, West Java Province. The method used in this study is descriptive with a qualitative approach, where data collection techniques are carried out through interviews, observation and documentation. And the factors that influence policy implementation using Edward III’s theory are the dimensions of communication, dimensions of resources, dimensions of disposition and dimensions of bureaucratic structure. The results of the research conducted show that the implementation of organizational structure on performance has not been followed up by equalization of positions in the preparation of SK and Tusinya. Efforts that can be made by the Depok city government are issuing a mayoral regulation regarding work mechanisms or equalization so that employees can work according to their scope of work